Financial fragility and financial stress during the COVID-19 crisis: evidence from Colombian households - Cardona-Montoya, Raul Armando (2022)
Purpose: Our findings indicate that workers with more financial education were more prepared to face the negative effects on their finances from COVID. This ability reduces the probability of becoming financially fragile and experiencing financial stress. Design/methodology/approach: The authors applied a survey questionnaire to 856 Colombian adults and used principal component analysis to build an index for each factor. Then, the authors used a linear regression model with the indexes to test our hypotheses and verify our results using a structural equation model. Findings: Our findings indicate that workers who have more financial education are more prepared to face the negative effects on their finances, which reduces the probability of becoming financially fragile and having financial stress. Research limitations/implications: The authors found that there is no significant relationship between financial literacy and financial fragility, neither between financial literacy and financial stress, so a better financial education will not lower financial fragility and stress unless it is being applied by households through better financial preparedness. Practical implications: It is important to highlight that the pandemic not only taught us to improve biosecurity measures but also that financial strength, ability to work remotely and income diversification were key factors in facing this adverse shock, the authors show that high levels of financial education have a positively relationship with the ability of individuals to manage their resources, so private and public institutions have to promote better financial education. Originality/value: This is the first study that applies the four different indexes to an emerging country (i.e. Colombia), and the first one to create and use a financial stress index.